Pollock and "the Blob": Impacts of a marine heatwave on walleye pollock early life stages. (7th October 2020) - Rogers, Lauren A.; Wilson, Matthew T.; Duffy‐Anderson, Janet T.; Kimmel, David G.; Lamb, Jesse F.
Abstract: The North Pacific marine heatwave of 2014–2016 (nicknamed "The Blob") impacted marine ecosystems from California to Alaska, USA, with cascading effects on fisheries and fishing communities. We investigated the effects of this anomalous ocean warming on early life stages of walleye pollock ( Gadus chalcogrammus ) in the Gulf of Alaska. In spring of 2015, pollock larvae were caught at record low levels relative to a 30‐year time series. Survival rates were low during the summer, and by late summer, numbers were further reduced, with very low abundances of juvenile (age‐0) pollock. Our analyses suggested multiple mechanisms for this decline: (a) Low‐saline conditions may have impacted egg buoyancy and survival; (b) population densities of zooplankton nauplii may have been too low to support first‐feeding larvae; (c) body condition of age‐0 pollock was poor and a bioenergetics model indicated that reduced quality of zooplankton prey, coupled with warmer temperatures, increased the ration required for positive growth by up to 19%, at a time when prey abundance was likely reduced. Thus, walleye pollock experienced a cascade of poor conditions for growth and survival through early life stages, resulting in the near disappearance of the 2015 year class in the population by the end of their first year. These impacts differ from previous warm years and emphasize the importance of looking beyond simple temperature–abundance relationships when predicting species responses to climate warming.